2003
DOI: 10.1104/pp.103.022939
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Redox Potential of Primary and Secondary Electron-Accepting Quinones in Photosystem II Confer Increased Resistance to Photoinhibition in Low-Temperature-Acclimated Arabidopsis

Abstract: Exposure of control (non-hardened) Arabidopsis leaves for 2 h at high irradiance at 5°C resulted in a 55% decrease in photosystem II (PSII) photochemical efficiency as indicated by F v /F m . In contrast, cold-acclimated leaves exposed to the same conditions showed only a 22% decrease in F v /F m . Thermoluminescence was used to assess the possible role(s) of PSII recombination events in this differential resistance to photoinhibition. Thermoluminescence measurements of PSII revealed that S 2 Q A Ϫ recombinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 54 publications
5
71
4
Order By: Relevance
“…It has been suggested that high q O in relation to q N is an indicator for high q O (Bukhov et al, 2001;Sane et al, 2003). We found q O /q N Figure 7.…”
Section: Dissipation Of Excess Energy Depends On the Aggregation Statsupporting
confidence: 48%
See 1 more Smart Citation
“…It has been suggested that high q O in relation to q N is an indicator for high q O (Bukhov et al, 2001;Sane et al, 2003). We found q O /q N Figure 7.…”
Section: Dissipation Of Excess Energy Depends On the Aggregation Statsupporting
confidence: 48%
“…Overwintering evergreen conifers seem to be able to shift between the dynamic and the sustained antenna quenching (q O ) modes for dissipating excess energy . Aside from NPQ of excess energy in the antenna, a zeaxanthin independent way of quenching has been described in the reaction center (RC; Ivanov et al, 2001Ivanov et al, , 2006Lee et al, 2001;Sane et al, 2003;Finazzi et al, 2004). In addition to antenna and RC quenching, excess energy can be funneled into a range of alternative electron sinks, most notably photorespiration (Osmond and Grace, 1995;Streb et al, 1998), the water-water cycle (Asada, 1999), and cyclic electron transport (Ivanov et al, 2001;Kanervo et al, 2005).…”
mentioning
confidence: 99%
“…In low-carbon medium, there is an imbalance between ATP supply and electron acceptor availability. Generally, lack of CO 2 is accompanied by an increase in the Q A reduction level (and, therefore, a strong increase in the chlorophyll a fluorescence signal; see above) but also a higher resistance to photoinhibition (Sane et al, 2003). Under conditions of high excitation pressure, there is increased cyclic electron flow around PSII via cytochrome b 559 (Buser et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In short, when PSII is excited by a very short flash of saturating light, Q A is fully reduced and fluorescence reaches its maximal value, after which it decreases with a rate dependent on reoxidation of Q A by PQ diffusing from the surrounding membrane domains. Thus, the kinetics of fluorescence decay depend on the rate of PQ diffusion to the PSII Q B site (Sane et al, 2003). Fluorescence recovery kinetics were clearly slower in koCP24 than in the wild type and koCP26, implying that the accessibility of the Q B site to PQ was restricted ( Figure 9).…”
Section: Kinetics Of Q a Reoxidationmentioning
confidence: 97%